Ultrasmall Co2P2O7 nanocrystals anchored on nitrogen-doped graphene as efficient electrocatalysts for the oxygen reduction reaction. (1st April 2019) - Li, Kaidi; Guo, Mingjing; Yan, Ya; Zhan, Ke; Yang, Junhe; Zhao, Bin; Li, Jianqiang
Abstract : A novel composite electrocatalyst with ultrasmall Co2 O2 P7 nanocrystals supported on nitrogen-doped graphene has been developed and exhibits remarkable ORR performance. Abstract : Although cobalt pyrophosphate (Co2 P2 O7 ) has shown promise as a potential electrocatalyst for the oxygen evolution reaction (OER), its electrocatalytic activity for the oxygen reduction reaction (ORR) has rarely been explored. In this work, a novel composite catalyst with in situ grown Co2 P2 O7 on nitrogen-doped graphene nanosheets (Co2 P2 O7 /N-rGO) was fabricated by a facile one-step pyrolysis method. Pyrolysis temperature was found to have a significant effect on the morphology, structure and ORR performance of the composites. The catalyst fabricated at 800 °C (Co2 P2 O7 /N-rGO-800) presented ultrasmall Co2 P2 O7 nanocrystals (below 5 nm) anchored on N-rGO and the highest pyridinic-N proportion. Benefiting from the full exposure of active sites on the ultrasmall Co2 P2 O7 nanocrystals, abundant pyridinic-N species and the synergistic effect of Co2 P2 O7 and N-doped graphene, optimized Co2 P2 O7 /N-rGO-800 not only demonstrates excellent ORR catalytic activity with a positive cathodic peak potential (0.823 V vs. 0.833 V of the commercial Pt/C catalyst), but also shows superior durability and methanol crossover resistance to Pt/C in alkaline solution. In addition, the composite catalyst also exhibits reasonable oxygen evolution reaction (OER) performance and impressive OER stability in KOH solution. These findings suggest that the Co2 P2 O7 /N-rGO catalysts may be promising candidates as oxygen electrocatalysts for future energy conversion applications.